2021
DOI: 10.3390/brainsci11111384
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and Ecstatic Experiences: The Role of the Insula

Abstract: Ecstatic epilepsy is a rare form of focal epilepsy in which the aura (beginning of the seizures) consists of a blissful state of mental clarity/feeling of certainty. Such a state has also been described as a “religious” or mystical experience. While this form of epilepsy has long been recognized as a temporal lobe epilepsy, we have accumulated evidence converging toward the location of the symptomatogenic zone in the dorsal anterior insula during the 10 last years. The neurocognitive hypothesis for the genesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Investigation of neural correlates of emotion, using electrophysiological and neuroanatomical methods, have mainly focused on fear‐related defensive behaviors. In animals, studies of conditioned fear responses 5 and fear extinction studies 6 demonstrate a spectrum of behaviors—flight, flight, and freeze—showing scalability 3 according to the proximity of the threat, which depend upon cortical and subcortical circuits, involving amygdala, hippocampus, and striatum (attention, action, and threat systems) and phylogenetically older circuits involving midbrain and medulla 8 . Distinction can be made between subjective (feeling, affective) and objective (behavioral) aspects of emotion, and it has been postulated that these may have different neural correlates 9 .…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Investigation of neural correlates of emotion, using electrophysiological and neuroanatomical methods, have mainly focused on fear‐related defensive behaviors. In animals, studies of conditioned fear responses 5 and fear extinction studies 6 demonstrate a spectrum of behaviors—flight, flight, and freeze—showing scalability 3 according to the proximity of the threat, which depend upon cortical and subcortical circuits, involving amygdala, hippocampus, and striatum (attention, action, and threat systems) and phylogenetically older circuits involving midbrain and medulla 8 . Distinction can be made between subjective (feeling, affective) and objective (behavioral) aspects of emotion, and it has been postulated that these may have different neural correlates 9 .…”
Section: Figurementioning
confidence: 99%
“…8 Distinction can be made between subjective (feeling, affective) and objective (behavioral) aspects of emotion, and it has been postulated that these may have different neural correlates. 9 Data on objective behavioral expressions of emotion predominantly come from animal (mainly nonprimate) models, 8,10 whereas human studies have used subjective and objective reports of emotion, using functional neuroimaging 11 or electrophysiological methods. 12 Epileptic seizures represent an interesting data source for studying emotional expression in humans.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These likely rival (or surpass) anything that could be achieved with exogenous compounds, or at least not safely, since endogenous mechanisms involve local release and natural clearance mechanisms. Further, it has been suggested that the moment of orgasm itself involves quasi-epileptiform dynamics in the form of explosive percolation through super-critical systems, potentially explaining some parallels between the neurophenomenology of orgasm and temporal lobe seizures with ecstatic auras (Asheim Hansen, & Brodtkorb, 2003;Arias, 2019;Chaton et al, 2018;Picard, Bossaerts, & Bartolomei, 2021) and related feelings of post-ictal relaxation, well-being, and spirituality (Devinsky & Lai, 2008;Picard & Craig, 2009). If these events happen in the context of another individual who is similarly altered, then bonding and potential co-mingling of various self-related processes may naturally arise.…”
mentioning
confidence: 99%